Pathomorphological study on gastric ulceration in horses - O. Stefanyk; L. Slivinska (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки, 2019)
Equine gastric ulcer syndrome (EGUS) is characterized by ulceration in the terminal esophagus, proximal (squamous) stomach, distal (glandular) stomach, and proximal duodenum. It is a common disease in all breeds and ages of horses and foals. Risk factors for EGUS include stress, transport high-energy feed confinement in stalls, intermittent feed, and intense exercise and racing. Horses are very sensitive to any environmental change, which is cause of high prevalence of gastric ulcers especially in racing horses. Taking into consideration of high prevalence of EGUS, our research work was based on pathomorfological and gross evaluation of gastric mucosa in different breeds of horses. Assessment of the severity of lesions is most commonly achieved by assigning a grade that describes the mucosal appearance at different anatomic sites. A variety of different systems have been published for the horses. 10 stomachs were removed from a mixed population post mortem. In our study pathological classification of lesion type was evaluated by two different scoring system, with scales ranging from 0–4. Samples from areas with lesion were taken for histopathology evaluation. EGUS was confirmed on stomachs of six horses. Lesions with different score mostly localized on squamous region near margo plicatus. Changes on squamous mucosa was confirmed on stomach of four horses as well as glandular region two horses. According to score systems mentioned in publication changes on gastric mucosa was measured up 1, 2, 3 score and were characterized as hyperceratosis, erosions and deeper lesion involving the mucosa, extending to the submucosa layer and hyperemia of glandular mucosa. The results of pathomorphological examination of the condition of the wall of the gastric mucosa and histological changes, the effectiveness of the submitted classification systems was established.